Beyond Resilience: How to Better Prepare for the Profound Disruption of the Anthropocene. (May 2016) - Kareiva, Peter; Fuller, Emma
Abstract: Human activity is dramatically shaping all of Earth's natural systems, producing unprecedented challenges for people and nature. Climate disruption, altered hydrology, and ecosystem degradation reflect both threats to human wellbeing and changes in the 'rules of the game' that make management difficult. While ecologists, conservationists and environmental scientists clamor for radical action to reverse these threats, their own management actions in response to climate are too often business as usual. I hypothesize that restrictive and often unspoken mental models of ecological and environmental science are robbing these managers and their institutions of the flexibility required to respond to the Anthropocene's uncertain changes. The three most profound mental traps are: (1) an undue emphasis on historical reference points; (2) an ecological concept of resilience that fails to reckon with the Anthropocene's dynamism; and (3) a precautionary bias against new technologies and dramatic interventions. Caught in these mental traps, environmentalists too often reject entrepreneurial experimental approaches that could make them more relevant to policymakers, corporations and other institutions that seek to respond more proactively to impending disruption. Abstract : Evolution has dealt with environmental change by random mutation and experimenting with novel variants – policy and management needs to take a lesson from evolution and do the same.